2018
DOI: 10.3390/w10070841
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infectious Noroviruses from Wastewater and Seawater Using PEMAXTM Treatment Combined with RT-qPCR

Abstract: Rapid detection of infectious noroviruses from environmental samples is essential to minimize the risk of norovirus outbreaks associated with environmental transmission. Reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) methods are rapid and sensitive, but cannot differentiate between infectious and non-infectious noroviruses. In this study, a PEMAX TM treatment followed by RT-qPCR (PEMAX TM -RT-qPCR) method was developed for murine norovirus and norovirus GI/GII, and evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Even if PMAxx showed to significantly affect the virus titers (Table S2), the high loads of viruses in the PMAxx-treated samples indicate the potential infectivity of detected viruses. Similarly, Gyawali and Hewitt (2018) evaluated the performance of PEMAX-RT-qPCR on influent and effluent water and found a high proportion of potentially infectious NoV GI and GII (i.e., 21 to 89% in influent, and 24 to 59% in effluent).…”
Section: Interlaboratory Study For the Detection And Quantification Of Potentially Infectious Enteric Viruses In Influent And Effluent Wamentioning
confidence: 99%
“…Even if PMAxx showed to significantly affect the virus titers (Table S2), the high loads of viruses in the PMAxx-treated samples indicate the potential infectivity of detected viruses. Similarly, Gyawali and Hewitt (2018) evaluated the performance of PEMAX-RT-qPCR on influent and effluent water and found a high proportion of potentially infectious NoV GI and GII (i.e., 21 to 89% in influent, and 24 to 59% in effluent).…”
Section: Interlaboratory Study For the Detection And Quantification Of Potentially Infectious Enteric Viruses In Influent And Effluent Wamentioning
confidence: 99%
“…Higher temperatures, which are known to denaturate the virus capsid, showed comparable results when analyzed with azo-dyes. Articles published by [34,[67][68][69] indicate that inactivation of Noroviruses GI/GII and the Hepatitis A virus, as well as Rotavirus and Aichivirus 1 after inactivation at temperatures between 50 • C and 95 • C was observable when PMA derived PMAxx, PMA, and EMA pretreatment was applied.…”
Section: Resultsmentioning
confidence: 99%
“…The technique, which has enabled the copy and quantification of fragments of the virus' genetic material through in-vitro replications, has been considered as reliable, sensitive, highly specific and the "gold standard" in the detection of low amounts of genetic material in different types of matrices (Corpuz et al 2020;Hamouda et al 2021). Earlier studies indicated that RT-qPCR methods were successfully able to determine the diversity and abundance of several viral pathogens in wastewater, including Adenovirus, Astrovirus, Enterovirus, Hepatitis A and E, Norovirus, Papillomavirus, Parechovirus, Polyomavirus, Rotavirus and Salivirus (O'Brien et al 2017;Bisseux et al 2018;Gyawali & Hewitt 2018;Adineh et al 2019;I. Ahmed et al 2019;Randazzo et al 2019).…”
Section: Methods Used To Detect the Sars-cov-2 In Wastewatermentioning
confidence: 99%